Distribution, evolution and structural properties of Wushenqi paleo-uplift in Ordos Basin, NW China - Danfeng MAO; Dengfa HE; Hongping BAO; Liubin WEI; Yanhua XU; Xiang CHENG; Junyi GOU; Saijun WU (Petroleum Exploration and Development, 2023)
This paper depicts the distribution of the Wushenqi paleo-uplift in the Ordos Basin by using the latest drilling and seismic data, and analyzes the tectonic evolution of the paleo-uplift with the support of Bischke curve and balanced section. The compressional Wushenqi paleo-uplift which developed in the Early Caledonian orogeny (Huaiyuan orogeny) is approximately a ellipse extending in S-N direction. Its long axis is about 194 km and short axis is about 55–94 km in nearly W-E direction. The denudation thickness and area of the Cambrian in the core are 170–196 m and 11 298 kmbrespectively. It was mainly formed during the Huaiyuan orogeny according to the chronostratigraphic framework. It was in the embryonic stage in the Middle–Late Cambrian, denuded after developed obviously at the end of Late Cambrian. The paleo-uplift of the 3rd member of the Ordovician Majiagou Formation was reactivated and reduced in area. In the sedimentary period of the Ma4 Member–pre-Carboniferous, the paleo-uplift experienced non-uniform uplift and denudation. It entered the stable period of burial and preservation in the Carboniferous and later period. The Wushenqi paleo-uplift was formed on the weak area of the basement and tectonic belts, into an compressional structure with irregular morphology, under the control of the non-coaxial compression in the south and north and the stress transmitted by the uplift in the basin. The Wushenqi paleo-uplift has a controlling effect on the sedimentary reservoirs and hydrocarbon accumulation.